Association between aortomitral continuity calcification and conduction disturbances following transcatheter aortic valve implantation with the balloon‐expandable Myval valve - Serkan Aslan; Aysel Türkvatan; Mehmet Kanyılmaz; Burçin Yılmaz; Dilara Pay; Kadir Sadıkoğlu; Hande Uysal; Gökhan Demirci; Mehmet Altunova; Serkan Kahraman; Mehmet Ertürk (Journal of Arrhythmia)
Abstract Background Given the anatomical proximity of the cardiac conduction system, aortomitral continuity calcification (AMCC) may contribute to conduction disturbances (CD) during transcatheter aortic valve implantation (TAVI) due to radial force on the AMCC. This study aimed to investigate the impact of AMCC on new‐onset CD in patients undergoing TAVI with the balloon‐expandable Myval valve. Methods This retrospective study included 160 patients who underwent TAVI. AMCC was assessed using Agatston and calcium volume scores from preprocedural computed tomography (CT). Multivariable logistic regression was used to identify independent predictors of CD. Results High‐grade atrioventricular block (HAVB) occurred in 13.1% of patients, and 17.5% required permanent pacemaker implantation (PPM). Patients with HAVB and PPM exhibited a higher prevalence of AMCC and significantly higher AMCC scores. An AMCC score >180 was an independent predictor of HAVB (OR, 5.58; 95% CI, 1.43–21.70; p = .013) and PPM (OR, 5.39; 95% CI, 1.75–16.55; p = .002). When classified by AMCC proximity type, right fibrous trigone (RFT)‐dominant calcification was a strong independent predictor of HAVB (OR, 9.22; 95% CI, 1.63–51.99; p = .012) and PPM (OR, 7.62; 95% CI, 1.91–30.38; p = .004). Prolonged QRS duration, greater implantation depth, and shorter membranous septum length were also independent predictors. Conclusion AMCC is a strong independent predictor of HAVB and PPM following TAVI, particularly with scores >180 or when AMCC is anatomically close to the RFT. Preprocedural CT‐based assessment of AMCC burden and proximity may improve risk stratification and procedural planning.